Exploring the Importance of Criminal Legal Aid: A Canadian Perspective - Pratt, Marcus; Farrow, Trevor CW (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
There is a growing global recognition that, in order to address the current access to justice crisis, more research, together with a better understanding of data, is needed. This article, through an examination of existing legal aid research primarily in the area of criminal law, explores some of what we know and do not know about the relative benefits and costs of providing different kinds of criminal legal aid services. Although not a comprehensive review of all available research, this article identifies data strengths and gaps and the need for further research and reforms.